2011
DOI: 10.1111/j.1440-1843.2011.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring air pollution: Use of early warning systems for public health

Abstract: Research confirming the detrimental impact poor ambient air quality and episodes of abnormally high pollutants has on public health, plus differential susceptibility, calls for improved understanding of this complex topic among all walks of society. The public and particularly, vulnerable groups, should be aware of their quality of air, enabling action to be taken in the event of increased pollution. Policy makers must have a sound awareness of current air quality and future trends, to identify issues, guide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 64 publications
1
78
0
1
Order By: Relevance
“…The use of satellite technology coupled with ground based instruments to gather real-time and continuous data respectively are needed to ensure air quality assessment. The use of telecommunication gadgets and mobile devices such as cellular phones with remote sensing applications can provide dynamic, temporally and spatially precise information of these pollutants (Kelly et al, 2012). The assessment must include identification of the source of pollution, its spatial distribution and the future trend; this will help policy makers to take decisive actions for remedy.…”
Section: Early Warning Systems Risks and Vulnerability Assessmentsmentioning
confidence: 99%
“…The use of satellite technology coupled with ground based instruments to gather real-time and continuous data respectively are needed to ensure air quality assessment. The use of telecommunication gadgets and mobile devices such as cellular phones with remote sensing applications can provide dynamic, temporally and spatially precise information of these pollutants (Kelly et al, 2012). The assessment must include identification of the source of pollution, its spatial distribution and the future trend; this will help policy makers to take decisive actions for remedy.…”
Section: Early Warning Systems Risks and Vulnerability Assessmentsmentioning
confidence: 99%
“…This last point will require consideration of personal privacy, data source anonymity and potential misuse or unwanted (by the people involved) use of the data that is captured. A final point, as discussed by [12], is that even if useful real-time environmental monitoring data is available, either from dedicated field researchers or crowd-sourced from the general population, we still lack ways of effectively communicating the appropriate information to people that might benefit from it. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…increased respiratory illness, cardiopulmonary morbidity, and premature mortality) concluded that nanoparticles can be considered potentially the most harmful of all pollutants. They can penetrate straight into the lungs and blood stream and, as recently has been revealed, act actively in the aging process [2,3]. Once this threat was highlighted, the problem of controlling the toxic emissions has become of great scientific and even political interest.…”
Section: Introductionmentioning
confidence: 99%